ESSENTIAL COMMODITY CONSUMPTION: A STUDY ON FOOD CONSUMPTION EXPENDITURE OF RURAL SOCIETY - Mohamad Ichwan; Patta Tope (Universitas Tadulako, 2020)
The primary commodity consumed by people is reflected in the highest expenditure to fulfill it within a specific period, the dominance of expenditure in all consumption expenditures indicates the importance of commodities in all households' consumption. This study aims to identify the dominant consumption patterns of food commodities using descriptive analysis of 6,178 households obtained through national secondary data from the 2017 national socio-economic survey (Susenas). Several commodities categorized by largest to smallest expenditure are the basis for determining the largest consumption expenditure as essential commodities. Based on the ranking of consumption expenditures, the three most prominent consumption groups were identified, namely: (1) rice, (2) rice with assortment of side dishes, and (3) fish. Rice, detected through 4,771 households, is the largest consumption commodity, and expenditure on this commodity increases in line with the rise in income, reflected in the mean value of expenditure which is higher in the increasing income group. The expenditure of rice with assortment of side dishes was detected through 3,150 households and had the same tendency as rice, particularly increased expenditure in the higher income groups. Fish consumption expenditure was detected through 3,488 households following the conditions for the two previous commodities, and expenditures increased with higher income. The increased expenditure on the consumption of essential commodities by income groups demonstrates that the tendency to consume is in accordance with Keynes's relationship between consumption and revenue. The higher the income, the greater the consumption expenditure. However, to a certain extent, the specific relationship is that the proportion of increased consumption expenditure decreases with higher income. Based on the elasticity coefficient, it was found that three essential commodities were normal goods. However, the level of consumption sensitivity to rice and fish income was higher than for processed food. In contrast to elasticity, the tendency to consume processed food is higher; the share of the increase in revenue is used to increase consumption of processed food, compared to adding rice and fish. This finding acts as provisional evidence that food consumption has undergone a fundamental change to become more consumptive.